A&T Gujarat Implementation Research Baseline Survey 2022: Pregnant Women - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset comes from the Pregnant Women Survey, conducted as part of the baseline for the Alive & Thrive (A&T) impact evaluation in Gujarat, India. The study assessed how systems-strengthening interventions and local governance efforts improved the quality and coverage of nutrition and health services during pregnancy.